2014
DOI: 10.1080/13811118.2014.957450
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Non-Suicidal Self-Injury: A Meta-Analytic Review

Abstract: The aim of this study was to conduct the first meta-analysis comparing risk for NSSI between sexual minority and heterosexual persons. Eleven published and 4 unpublished studies were reviewed, describing associations between sexual orientation and NSSI in 7,147 sexual minority and 61,701 heterosexual participants. The overall weighted effect size for the relationship between sexual orientation and NSSI using a random-effects model was OR = 3.00 (95% CI = 2.46-3.66), indicating a medium-to-large effect. Sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 69 publications
5
76
0
Order By: Relevance
“…It is noteworthy, however, that our sample size was comparable to another recently published meta-analysis on NSSI (Batejan, Jarvi, & Swenson, 2014). Nevertheless, it is important to acknowledge that our quantitative results are based on a small set of studies (particularly our analyses assessing whether the different facets of impulsivity were differentially related to NSSI), and it is possible that unpublished null findings on the link between impulsivity and NSSI could reduce the strength of association identified in the metaanalyses.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is noteworthy, however, that our sample size was comparable to another recently published meta-analysis on NSSI (Batejan, Jarvi, & Swenson, 2014). Nevertheless, it is important to acknowledge that our quantitative results are based on a small set of studies (particularly our analyses assessing whether the different facets of impulsivity were differentially related to NSSI), and it is possible that unpublished null findings on the link between impulsivity and NSSI could reduce the strength of association identified in the metaanalyses.…”
Section: Discussionmentioning
confidence: 73%
“…The present effect size was comparable to findings from other meta-analyses on NSSI (to our knowledge, the only two meta-analyses on NSSI). Klonsky and Moyer (2008) found a small effect size (d = .47) between childhood sexual abuse and impulsivity, and Batejan et al (2014) found a moderate effect size between sexual orientation and impulsivity (d = .61; effects were converted to Cohen's d, see Borenstein, Hedges, Higgins, & Rothstein, 2009). …”
Section: Discussionmentioning
confidence: 98%
“…2,3 These associations have been reported in cross-sectional surveys across the world, in adults 2,3 and adolescents. 4,5 However, there is little longitudinal research on when increased risk for these mental health problems emerges and how it develops over time.…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish study of adolescents aged 15-17 years, 11.1% of the girls and 2.3% of the boys fulfilled the criteria for NSSI disorder (NSSID) according to DSM-5 (Zetterqvist, Lundh, Dahlstrom, & Svedin, 2013). Adolescents with a non-heterosexual orientation have been found to be at particularly higher risk of NSSI (Batejan, Jarvi, & Swenson, 2015).…”
Section: Self-injurious Behaviourmentioning
confidence: 99%